Serum autoantibody reactivity in bullous pemphigoid is associated with neuropsychiatric disorders and the use of antidiabetics and antipsychotics: a large, prospective cohort study. (15th July 2022) - Dikmen, H.O.; Yilmaz, K.; Benoit, S.; Bernard, P.; Drenovska, K.; Gerdes, S.; Gläser, R.; Günther, C.; Homey, B.; Horváth, O.N.; Huilaja, L.; Joly, P.; et al.
Abstract: Background: Bullous pemphigoid (BP), the by far most frequent autoimmune blistering skin disease (AIBD), is immunopathologically characterized by autoantibodies against the two hemidesmosomal proteins BP180 (collagen type XVII) and BP230 (BPAG1 or dystonin). Several comorbidities and potentially disease‐inducing medication have been described in BP, yet a systematic analysis of these clinically relevant findings and autoantibody reactivities has not been performed. Objective: To determine associations of autoantibody reactivities with comorbidities and concomitant medication. Methods: In this prospective multicenter study, 499 patients diagnosed with BP in 16 European referral centers were included. The relation between anti‐BP180 NC16A and anti‐BP230 IgG ELISA values at the time of diagnosis as well as comorbidities and concomitant medication collected by a standardized form were analysed. Results: An association between higher serum anti‐BP180 reactivity and neuropsychiatric but not atopic and metabolic disorders was observed as well as with the use of insulin or antipsychotics but not with dipeptidyl peptidase‐4 (DPP4) inhibitors, inhibitors of platelet aggregation and L‐thyroxine. The use of DPP4 inhibitors was associated with less anti‐BP180 and anti‐BP230 reactivity compared with BP patients without these drugs. This finding was even more pronounced when compared with diabetic BP patients without DPP4 inhibitors. Associations between anti‐BP180 and anti‐BP230 reactivities were also found in patients using insulin and antipsychotics, respectively, compared with patients without this medication, but not for the use of inhibitors of platelet aggregation, and L‐thyroxine. Conclusion: Taken together, these data imply a relation between autoantibody reactivities at the time of diagnosis and both neuropsychiatric comorbidities as well as distinct concomitant medication suggesting a link between the pathological immune mechanisms and clinical conditions that precede the clinically overt AIBD.